Optimal Use of Jak Inhibitors and Biologics for Atopic Dermatitis on the Basis of the Current Evidence - Masahiro Kamata; Yayoi Tada (JID Innovations, 2023)
Recently, Jak inhibitors such as baricitinib, upadacitinib, and abrocitinib were approved for the treatment of atopic dermatitis (AD) in addition to biologics, including dupilumab, tralokinumab, and nemolizumab. The increase in treatment options can be a benefit to patients with AD. Meanwhile, it could make it difficult for physicians to choose the best treatment among those treatment options. Biologics and Jak inhibitors differ in efficacy, safety, route of administration, and whether or not there is a concern about immunogenicity in addition to the evidence on comorbidities. Among the three Jak inhibitors, the degree of inhibition of signal transducer and activator of transcription differs in each Jak inhibitor. Therefore, the efficacy and safety profiles of the three Jak inhibitors are different. Physicians who treat patients with AD with Jak inhibitors and biologics need to understand the current evidence and choose the best treatment for individual patients. In this review, we discuss how integrating knowledge of the mechanisms of action of Jak inhibitors and biologics, the potential significant adverse events of these drugs, and the age and comorbidities of the patient can help achieve optimal clinical benefit for patients with moderate-to-severe AD refractory to topical agents.